Robotic stereotactic radiosurgery for intracranial meningiomas in elderly patients: assessment of treatment efficacy and safety - Früh, Anton; Bodnar, Bohdan; Nachbar, Marcel; Gradhand, Julia; Kalinauskaite, Goda; Rubarth, Kerstin; Truckenmueller, Peter; Kaul, David; Zips, Daniel; Vajkoczy, Peter; Senger, Carolin; Acker, Güliz (Frontiers in Oncology, 2024)
Purpose: Stereotactic radiosurgery (SRS) has been increasingly used to treat intracranial pathologies in elderly patients. The treatment efficiency of SRS has been demonstrated in meningiomas, with excellent local control. We aimed to analyze the safety of robotic SRS in elderly patients with meningiomas.We searched for patients with suspected WHO °I meningioma ≥ 60 years old, who underwent Cyberknife (CK) SRS from January 2011 to December 2021. Tumor localization was categorized using the "CLASS" algorithmic scale. Tumor response was evaluated using the Response Assessment in Neuro-Oncology (RANO) criteria for meningiomas. Adverse effects were graded using the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 and a cox regression was performed to investigate possible predictors.We identified 82 patients with 102 CK-treated lesions that matched the criteria for the first SRS. The median age was 70 [IQR 64-75] years, and 24.3% of the patients were aged > 75 years. Multiple lesions (up to six) were treated in 14.1% of the SRS-sessions. A previous surgery was performed in 57.3% of lesions, with a median time interval of 41 [IQR 10 -58] months between the initial surgical procedure and the SRS treatment. In 47.9% of cases, CLASS 3 meningiomas at highrisk locations were irradiated. Single fraction radiosurgery was applied to 62.5% of the lesions, while in the remaining cases multi-session SRS with three to five fractions was used. During the median follow-up period of 15.9 months, lesion size progression was observed in 3 cases. Karnofsky Performance Status (KPS) declined by ≥ 20 points in four patients. Adverse effects occurred in 13 patients, while only four patients had CTCAE ≥2 toxicities. Hereby only one of these toxicities was persistent. The occurrence of complications was independent of age, planned target volume (PTV), high-risk localization, and surgery before SRS.The data indicates that SRS is a safe, efficient, and convenient treatment modality for elderly patients with meningioma, even at high-risk locations